Effect of halloysite on structure and properties of melt-drawn PCL/PLA microfibrillar composites - I. Kelnar; J. Kratochvil; I. Fortelny; L. Kapralkova; A. Zhigunov; V. Khunova; M. Nevoralova (eXPRESS Polymer Letters)
The study deals with the modification of mechanical properties of poly (!-caprolactone) (PCL)/poly(lactic acid) (PLA) system using the microfibrillar composite (MFC) concept. As the in-situ formation of PLA fibrils by melt drawing was impossible due to flow instability during extrusion, the system was modified by adding halloysite nanotubes (HNT) using different mixing protocols. The resulting favourable effect on the rheological parameters of the components allowed successful melt drawing. Consequently, PLA fibrils formation combined with the reinforcement of components by HNT and increased PLA crystallinity lead to a biocompatible and biodegradable material with good performance suitable for a broad range of applications. The best results, comparable with analogous MFC modified with layered silicate (oMMT), have been achieved at a relatively low content of HNT of 3%, in spite of its lower reinforcing ability in a single nanocomposite. This indicates that modifying MFC by HNT, including fibrils and interface parameters, is more complex in comparison with the undrawn system.